Motor cortex hemodynamic response to goal-oriented and non-goal-oriented tasks in healthy subjects - Lacerenza, Michele; Frabasile, Lorenzo; Buttafava, Mauro; Spinelli, Lorenzo; Bassani, Elisa; Micheloni, Francesco; Amendola, Caterina; Torricelli, Alessandro; Contini, Davide (Frontiers in Neuroscience, 2023)
Background: Motor disorders are one of the world's major scourges, and neuromotor rehabilitation is paramount for prevention and monitoring plans. In this scenario, exercises and motor tasks to be performed by patients are crucial to follow and assess treatments’ progression and efficacy. Nowadays, in clinical environments, quantitative assessment of motor cortex activities during task execution is rare, due to the bulkiness of instrumentation and the need for immobility during measurements (e.g., functional magnetic resonance imaging (MRI)). Functional near-infrared spectroscopy (fNIRS) can contribute to a better understanding of how neuromotor processes work by measuring motor cortex activity non-invasively in freely moving subjects. Aim: exploit fNIRS to measure functional activation of the motor cortex area during arm-raising actions. Design: All subjects performed three different upper limbs motor tasks: arm raising (non-goal-oriented), arm raising and grasping (goal oriented) and assisted arm raising (passive task). Each task was repeated ten times. The block design for each task was divided into five seconds of baseline, five seconds of activity, and fifteen seconds of recovery. Population: sixteen healthy subjects (11 males and 5 females) with an average (+/- standard deviation) of 37.9 (+/- 13.0) years old. Methods: Cerebral hemodynamic responses have been recorded in two locations, motor cortex (activation area) and prefrontal cortex (control location) exploiting commercial time-domain fNIRS devices. Haemodynamic signals were analyzed, separating the brain cortex hemodynamic response from extracerebral hemodynamic variations. Results: The hemodynamic response was recorded in the cortical motor area for goal-oriented and not-goaloriented tasks, while no response was noticed in the control location (prefrontal cortex position). Conclusions: This study provides a basis for canonical upper limb motor cortex activations that can be potentially compared to pathological cerebral responses in patients. It also highlights the potential use of TD-fNIRS to study goal-oriented versus non-goaloriented motor tasks. Impact: The findings of this study may have implications for clinical rehabilitation by providing a better understanding of the neural mechanisms underlying goal-oriented versus non-goal-oriented motor tasks. This may lead to more effective rehabilitation strategies for individuals with motor disorders and a more effective diagnosis of motor dysfunction supported by objective and quantitative neurophysiological readings.